Analisa dan Perancangan Aplikasi Cuti atau Ijin Karyawan Menggunakan Aplikasi Berbasis Web - Ananta Dicapriyo; Elbino Andreas; Firmansyah Firmansyah; Endar Nirmala; Irpan Kusyadi (Program Studi Teknik Informatika Universitas Pamulang, 2021)
Employees as one element in a company have rights and obligations to the company. One of the rights for employees is leave or permission for a certain time. The obligation of a company is to provide such leave or permission. In the process of applying for leave or employee permits so far, many use conventional processes. Conventional here means still using a form in the form of a sheet of paper leave or permission and must be sent to various parties for approval. This will take a long time and is not in line with the Go Green Program that is being carried out by many companies. Reduce, Re-use, Recycle and Replace are the four concepts of the Go Green program. Replacing the application for leave or permission that has been using a form (paper) by using a web-based application program is a step forward by the company to implement the Go Green concept. Web-based application programs in addition to reducing paper usage also do not require large physical data storage areas. This can be realized by making a web-based leave application which is certainly easier in terms of access to all employees. Meanwhile, data storage can be stored in cloud storage media. In this study, an application design will be made using UML (Unified Modeling Language) to be used as a reference during development. UML provides many diagrams, but in this study only a few diagrams were used. The results of the study indicate that application design using UML can facilitate communication between stakeholders, can make it easier for programmers to translate into programming languages. Using UML can reduce application creation errors and speed up completion.